2015
DOI: 10.3233/bme-151341
|View full text |Cite
|
Sign up to set email alerts
|

Finite element analysis to study the effects of using CAD/CAM glass-fiber post system in a severely damaged anterior tooth

Abstract: Abstract.To investigate the stress distribution of a severely damaged maxillary anterior tooth restored with a computer-aided design/computer-aided manufacturing (CAD/CAM) glass-fiber post system. Twelve models were fabricated with different alveolar bone levels and cervical dentin wall thicknesses and studied using a two-dimensional finite element method. A force of 100 N was applied to the lingual surface of the crown at 45 degrees, and the maximum von Mises stress was calculated. A higher stress level was o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 21 publications
(22 reference statements)
0
8
0
2
Order By: Relevance
“…To our knowledge, no previous study has investigated direct scanning of the post space. Several studies used different indirect techniques for digital data acquisition of the post space (23)(24)(25)(26)(27)(28)34). Lee et al scanned stone models of the post space to custom-fabricate the fiber post and core restoration (23,24).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…To our knowledge, no previous study has investigated direct scanning of the post space. Several studies used different indirect techniques for digital data acquisition of the post space (23)(24)(25)(26)(27)(28)34). Lee et al scanned stone models of the post space to custom-fabricate the fiber post and core restoration (23,24).…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Bittner et al (34), acrylic resin patterns were scanned to CAD/ CAM-fabricate a zirconia post and core. The scanning methods used were not specified in recent studies of CAD/CAM glass fiber posts by Chen et al (27,28). In addition, no studies have examined the usefulness of procedures for digital acquisition of the post space.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, fiber-reinforced composite blocks were used to CAD/CAM fabricate the fiber posts for irregularly shaped or large root canals. [ 4 5 6 ] Furthermore, according to the literature, digital images of the prepared tooth required for CAD/CAM fabrication of the restoration can be obtained in three ways: by direct intraoral scanning, by scanning the impressions, or by scanning the stone models. Research has shown that both impressions and stone replicas can be digitized with high reliability.…”
Section: Introductionmentioning
confidence: 99%